2015
DOI: 10.1182/blood-2014-07-587337
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ3 acting as membrane receptor for thyroid hormones mediates angiogenesis in malignant T cells

Abstract: Key Points• We elucidate a molecular mechanism by which thyroid hormones sustain TCL survival.• We demonstrate that the membrane receptor of THs, integrin avb3, constitutes a potential target for TCL.The interaction of lymphoid tumor cells with components of the extracellular matrix via integrin avb3 allows tumor survival and growth. This integrin was demonstrated to be the membrane receptor for thyroid hormones (THs) in several tissues. We found that THs, acting as soluble integrin avb3 ligands, activated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 29 publications
8
101
0
1
Order By: Relevance
“…In line with our observations, transduction of the thyroid hormone signal via integrin avb3 was shown to lead to transcription of angiogenesis-relevant genes FGF2 and VEGF in the chorioallantoic membrane (CAM) model, as well as in heart and T-cell lymphoma (Luidens et al 2010, Cayrol et al 2015. A direct effect of thyroid hormones on inflammatory mediators such as IL6 has been tentatively proposed based on the inhibition of proinflammatory cytokines by the iodothyronine antagonist tetrac (Hercbergs et al 2012).…”
Section: Discussionsupporting
confidence: 61%
“…In line with our observations, transduction of the thyroid hormone signal via integrin avb3 was shown to lead to transcription of angiogenesis-relevant genes FGF2 and VEGF in the chorioallantoic membrane (CAM) model, as well as in heart and T-cell lymphoma (Luidens et al 2010, Cayrol et al 2015. A direct effect of thyroid hormones on inflammatory mediators such as IL6 has been tentatively proposed based on the inhibition of proinflammatory cytokines by the iodothyronine antagonist tetrac (Hercbergs et al 2012).…”
Section: Discussionsupporting
confidence: 61%
“…10.3), Patel et al reported that the viscoelastic properties of these hy- drogels are independent of their composition of adhesive additives-which has a unique effect on cell spreading, viability, and proliferation of cervical cancer and leukemia cell line models. Such engineered systems provide a platform to modulate the behavior of cancer cells and decouple some of the underlying microenvironment factors that induce tumorigenesis, affect tumor growth, and further tumor progression [35].…”
Section: Modulation Of 3d Tumor Microenvironmentmentioning
confidence: 99%
“…Jednakże w obecnym stanie wiedzy przyjęcie udziału hormonów tarczycy w patogenezie glejaka wielopostaciowego może już mieć wymiar praktyczny. Obniżenie stężenia TH w surowicy przedłużało remisje i czas przeżycia u chorych z glejakiem wielopostaciowym, który w GBM jest dramatycznie krótki [18,19], a stosowanie metabolitu T4-TRAK (kwas tetrajodotyrooctowy) w badaniach in vitro i na liniach komórkowych hamowało proliferację komórek glejaka oraz aktywność VEGF -ważnego regulatora stymulującego neoangiogenezę w procesach nowotworowych [88]. W tym samym czasie podanie TRAK zwiększało proces apoptozy [60].…”
Section: Polish Versionunclassified
“…Reduction of TH levels in blood serum prolonged the remission and lifespan in patients with glioblastoma multiforme; generally the patients' lifespan is extremely short in GBM [18,19]. The local application of T4 -TRAK metabolite (tetraiodothyroacetic acid) in studies conducted in vitro and on cell lines inhibited glial cell proliferation and activity of vascular endothelial growth factor (VEGF), an important stimulator of neo-angiogenesis in oncology [88]. At the same time, TRAK enhanced the apoptosis process [60].…”
Section: Prace Poglądowementioning
confidence: 99%